Spermatozoa motility and viability of turkey (Meleagris gallopavo) semen in egg yolk nanoparticles-phosphate buffered saline extender at 3-5°C storage - Nabila Ayu Saraswati; Herry Agoes Hermadi; Tri Wahyu Suprayogi; Tatik Hernawati; Eka Pramyrtha Hestianah (Ovozoa: Journal of Animal Reproduction, 2024)
This study aimed to evaluate the spermatozoa motility and viability of turkey semen extended with egg yolk nanoparticles-PBS extender at various concentrations, stored at 3-5°C. Semen was collected from two turkeys and divided into four treatment groups. Group T0 consisted of fresh turkey semen extended with 20% (v/v) fresh egg yolk in phosphate-buffered saline (PBS). Groups T1, T2, and T3 consisted of fresh turkey semen extended with 5, 10, and 20% (v/v) egg yolk nanoparticles in PBS, respectively. Extended semen was stored in a refrigerator (3-5°C), and progressive spermatozoa motility and viability were evaluated every two hours until spermatozoa motility decreased to 40%. The results showed that turkey semen in T3 extender containing 20% ​​egg yolk nanoparticles in PBS was able to maintain spermatozoa motility for up to eight hours, better than T0 and T2 extenders which supported spermatozoa motility for six hours. In contrast, T1 extenders only support spermatozoa motility for four hours. T3 extenders were also able to maintain spermatozoa viability for up to eight hours, while T0, T1 and T2 extenders could only support viability for 6 hours. The extender with 20% egg yolk nanoparticles in PBS was significantly better (p <0.05) in maintaining spermatozoa quality compared to those with 5 and 10% egg yolk nanoparticles, as well as the extender with 20% fresh egg yolk. In conclusion, 20% egg yolk nanoparticles in PBS semen extender was effective in maintaining the motility and viability of turkey (Meleagris gallopavo) spermatozoa stored at 3-5°C for up to eight hours.